Trends and Planning to use Contraception Tools in Women of Childbearing Age - Irma Muslimin; Hadmawaty Hamzah; Sukardi Sukardi; Andi Salim (Indonesian Journal of Global Health Research, 2020)
The implementation of family planning can reduce the burden of development for the realization of the happiness and welfare of the people of Indonesia. The choice of an appropriate contraceptive method and following the conditions and needs can prevent a significant population growth rate. This study aims to analyze trends in the use of contraceptives and planning for contraceptive use among women of childbearing age in the province of West Sulawesi. The design used in this study was a cross-sectional survey using secondary data sources from the 2017 IDHS West Sulawesi province. The study population was all merried women in Indonesia with a sample size of 1682 peoples. The results showed that age group, education level, residence, and socioeconomic status influence the propensity for use and planning for the use of contraceptives. Whereas literacy only affects the planning of contraceptive use. A special approach is needed for women and their husbands to convince them of the benefits of using contraceptive devices to prosper their lives.